Immune System Involvement in the Pathogenesis of JC Virus Induced PML: What is Learned from Studies of Patients with Underlying Diseases and Therapies as Risk Factors - Monaco, Maria Chiara G.; Major, Eugene O. (Frontiers in Immunology, 2015)
The human polyomavirus JC PyV lytic infection of oligodendrocytes in the human brain results in the demyelinating disease progressive multifocal leukoencephalopathy, PML. JCV is a common virus infection in the population that leads to PML in patients with underlying diseases and therapies that cause immune deficiencies or modulate immune system functions. Patients may have high levels of antibody to JCV that does not protect them from PML nor clear the infection once PML is established. Cell mediated immunity plays a more effective role in clearing initial or reactivated JCV infection before PML occurs. However patients with underlying diseases and therapies for treatment are at high risk for PML. MS patients on natalizumab are one of the categories with the highest incidence of PML. Natalizumab is a humanized monoclonal antibody targeting α4 integrins that prevents inflammatory cells from entering the brain and it has been used as a treatment for MS. A number of studies have investigated the occurrence of PML in these patients and their cell mediated immune profile that might gain insight into the mechanism that ties natalizumab with a high risk of developing PML. It seems that cells of the immune system participate in the pathogenesis of PML as well as clearance of JCV infection.